2D multichannel seismic reflection sorted data (GI Gun) of RV SONNE cruise SO232 in 2014 to the Mozambique Ridge, seismic reflection profile AWI-20140204 - Gabriele Uenzelmann-Neben (PANGAEA, 2025)
Seismic reflection data collected on the Mozambique Ridge during cruise SO232 with RV Sonne in 2014. 4 GI-guns were used a seismic source, the data were recorded with a 3000 m (active length) long digital streamer. The data are CDP-sorted. No gain, filter or mute have been applied. The data are in SEGY format. See cruise report (Uenzelmann-Neben, 2014) or ReadMe file for more information on acquisition parameters.